2010
DOI: 10.1146/annurev-matsci-070909-104529
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Composites Near Percolation

Abstract: Dramatic changes in the physical properties of composites occur when filler particles form a percolating network through the composite, particularly when the difference between the properties of the constitutive phases is large. By use of electric conductivity and dielectric properties as examples, recent studies on the physical properties of composites near percolation are reviewed. The effects of geometric factors and intrinsic properties of the fillers and the matrix, and especially of the interface between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
637
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 877 publications
(683 citation statements)
references
References 104 publications
24
637
2
2
Order By: Relevance
“…As it can be seen in Figure 8a, the permittivity level did not change as the applied frequency increased, which is in accordance with the behavior commonly observed for insulating materials such as epoxy and GF [34]. Due to the insulating nature of GO, coating of GF with GO did not provide any capacitive properties to Ep-GO-GF composite.…”
Section: Dielectric Propertiessupporting
confidence: 86%
“…As it can be seen in Figure 8a, the permittivity level did not change as the applied frequency increased, which is in accordance with the behavior commonly observed for insulating materials such as epoxy and GF [34]. Due to the insulating nature of GO, coating of GF with GO did not provide any capacitive properties to Ep-GO-GF composite.…”
Section: Dielectric Propertiessupporting
confidence: 86%
“…The dielectric constant of such a nanocomposite diverges at the percolation threshold f c , at which suffi cient nanoparticles are present to form a long-range connected network . 12 Many experiments have shown that, near to f c , the dielectric constant of the composite can become unbounded and extraordinarily high compared to that of the dielectric matrix. This composite effect comes from many conductive nanoparticles being isolated by thin dielectric layers, thus forming nanocapacitors.…”
Section: 10mentioning
confidence: 99%
“…According to percolation theory, a composite's dielectric and conductive properties will enhance extraordinarily when its filler concentration is close to the percolation threshold. 9,20 The increases in dielectric permittivity and conductivity of PVDF#1 over PVDF#0 likely resulted from the percolation effect. These results demonstrate that magnetic field treatment may induce the percolation effect at a low loading of 5 vol.% and enhance the interfacial polarization effect, improving the dielectric permittivity of the composite by several orders of magnitude.…”
Section: B Dielectric Properties Of Pvdf and The Untreated Pvdf Compmentioning
confidence: 99%
“…The loss tangent of PVDF#1 was as high as 10 3 at 10 Hz; as the frequency increased, the loss tangent increased slightly and then decreased dramatically above 10 3 Hz, which may have been caused by the percolation effect enhancing the conductivity. 13,20 The loss tangents of PVDF#2 FIG. 7.…”
Section: B Dielectric Properties Of Pvdf and The Untreated Pvdf Compmentioning
confidence: 99%
See 1 more Smart Citation